A new species of frogfish of the genus Histiophryne (Teleostei: Lophiiformes: Antennariidae) from Lombok and Komodo, Indonesia - Arnold, Rachel J. (Zootaxa, 2012)
Histiophryne pogonius, a new species of frogfish of the teleost order Lophiiformes, family Antennariidae, is describedfrom a total of five specimens: three collected in shallow waters surrounding Lombok, Indonesia, one reportedly from thenearshore waters of Cebu, Philippines, and a photograph of a specimen from Komodo Island, Indonesia. The new taxondiffers from its congeners in having an extremely small illicium and esca, barely discernible even with aid of a dissectingmicroscope; dark pink pigmentation overlaying a pale pink background, including a dark pink basidorsal spot; a smallwhite encrusted patch of skin always present posterior to pectoral-fin origin, with similar patches sometimes present oncheeks; body everywhere covered with small dark reddish to black spots, including lips and outer margins of the sclera,spots encircled by a thin white ring; cheeks with shallow depressions, giving head a pitted appearance; head lightlycovered with cutaneous cirri, especially around edges of opercle; upper and lower lips with short cutaneous cirri; andgenetic divergence in mitochondrial gene cytochrome oxidase c subunit I (COI). The new species is described andcompared with its congeners, and a phylogenetic tree based on the nuclear recombination activation gene-2 (RAG2) and mitochondrial cytochrome oxidase c subunit I (COI) and 16S genes is presented.